Risk factors of Diabetes and its Comorbidities Among Elderly in India: Evidence from Longitudinal Aging Study (LASI) - Chiero, Vekutulu; KC Das (National Journal of Community Medicine, 2023)
Context/Background: Chronic diseases like diabetes are at risk of developing heart disease. Therefore, it is crucial to identify the high-risk population, which would help policymakers and interventionists focus on vulnerable groups. This study aims to determine the prevalence, risk factors, and coexistence of other diseases with diabetes. Methodology: Secondary data from Longitudinal Aging Study in India (LASI), Wave 1 (2017-18) was used for the study. A sample of 65,562 men and women aged 45 years and above have been included in the analysis. Univariate, bivariate, and multivariate statistical analysis was used for the analysis. Results: Overall, (12.4%) of Indians have self-reported diabetes. The prevalence of diabetes is (12.9%) among men and (11.9%) among women. Geographic variations were observed with higher rates in south India. Depression, lack of physical activity, obesity, increase in age, family history of diabetes, higher level of education, and wealth quintile were all significant risk factors for diabetes among men and women. Diabetes is associated with other chronic conditions such as heart disease, hypertension, and diseases of the bones and joints. Conclusions: Although self-reported data underestimate the disease burden, it is evident that the prevalence of self-reported diabetes is high. India should address the risk of diabetes by promoting and encouraging a healthy lifestyle.